Nurturing artistic creativity among Chinese female adolescents in Hong Kong: a qualitative study - Chow, Mei Fung (2019)
Creativity is an important ability of an individual which enables her or him to live better, raise their quality of life and develop competitive advantage in the changing society. Little research has been focused on the learning and development of artistic creativity among Chinese female adolescents. This qualitative life history research introduces and explores what constitutes artistic creativity among Chinese female adolescents in Hong Kong and how this is developed. Seven Chinese female adolescents were analysed and are presented in this study. Their learning and development of artistic creativity is interpreted in terms of ideas drawn mainly from the literature on creativity, and the influence of personal and environmental factors on the development of artistic creativity in the visual arts. Based on the life history narratives of the participants, new insights are derived as to what personal and environmental factors may lead to the development of artistic creativity, and how Visual Arts teachers and education institutions can play a vital role in nurturing the artistic creativity among Chinese female adolescents in Hong Kong. The study found that some factors, like motivation and teachers’ influence, have a more significant and positive influence in fostering the artistic creativity among Chinese female adolescents in Hong Kong. Visual Arts teachers need to act as facilitators to motivate students, and provide learning opportunities and supportive classroom environment to nurture the artistic creativity among female adolescents. This thesis contributes to the academic understanding on the learning and development of artistic creativity in the visual arts. The study makes a number of contributions with implications for teachers and education institutions to nurture the artistic creativity among Chinese female adolescents with reference to the complex environment in Hong Kong.